2008
DOI: 10.1016/j.ydbio.2008.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and patterning of the snake dentition are dependent on Sonic Hedgehog signaling

Abstract: Here we take the first look at cellular dynamics and molecular signaling in the developing snake dentition. We found that tooth formation differs from rodents in several respects. The majority of snake teeth bud off of a deep, ribbon-like dental lamina rather than as separate tooth germs. Prior to and after dental lamina ingrowth, we observe asymmetries in cell proliferation and extracellular matrix distribution suggesting that localized signaling by a secreted protein is involved. We cloned Sonic hedgehog fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
117
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(127 citation statements)
references
References 60 publications
8
117
1
1
Order By: Relevance
“…3) appear to develop entirely within the surface epithelial layer rather than through invagination of the entire tooth germ. This invaginated dental epithelium is considered essential for tooth replacement in all other known vertebrate dentitions (17,21,32,33). The first-generation parasymphyseal tooth germs in Monotrete spp., which also begin their development in a superficial position, later invaginate deep into the underlying mesenchyme.…”
Section: Resultsmentioning
confidence: 99%
“…3) appear to develop entirely within the surface epithelial layer rather than through invagination of the entire tooth germ. This invaginated dental epithelium is considered essential for tooth replacement in all other known vertebrate dentitions (17,21,32,33). The first-generation parasymphyseal tooth germs in Monotrete spp., which also begin their development in a superficial position, later invaginate deep into the underlying mesenchyme.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the chondrichthyan and amphibian species studied, the replacing series of tooth germs in polyphyodont squamates are united by a permanent dental lamina linking the developing teeth in a chain to the functional dentition, and the oral surface [10,12,47,48]. At birth 3-4 developing generations of teeth are found linked to the dental lamina, making a developmental series ready to replace the functional tooth.…”
Section: Reptilesmentioning
confidence: 93%
“…This bulge has been found during development in all toothed reptile species examined, even those with only one set of functional teeth [44,46,55]. The squamate successional lamina is a region of high proliferation and low apoptosis (programmed cell death) [47,56]. Fate mapping of the successional lamina in the snake has shown that the cells in the successional lamina contribute both to the new generations of teeth and are retained at the tip of the lamina [10].…”
Section: Reptilesmentioning
confidence: 95%
“…Shh and Fgf8 are expressed in the dental lamina in mouse (Bitgood and McMahon, 1995;Kettunen and Thesleff, 1998). Shh is also expressed in the dental lamina of snakes (Buchtova et al, 2008), shrews (Yamanaka et al, 2007), and catsharks (Smith et al, 2009), suggesting a strong conservation at this early stage of tooth development and a role in the generation of replacement teeth.…”
Section: Comparing Mouse Dental Developmental Genetics To Monodelphismentioning
confidence: 99%